Peran Kesetaraan Gender dalam Kemampuan Kepemimpinan Siswa di Sekolah Dasar - Al-Adzillah, Nabila; Fikriyah, Fikriyah; Mimin Darmini (CV. Ulil Albab Corp, 2024)
Student leadership is one of the student abilities that need to be developed. This research is motivated by the low leadership ability of female students because they are not given the opportunity to lead equally with male students. This study aims to determine students' leadership abilities, understanding of student gender equality and gender equality analysis of student leadership abilities. The approach used in this research is a qualitative approach with descriptive methods. The subjects of this research are students, principals and teachers. The techniques used in this research are observation and interview. The results showed that the understanding of gender equality is characterised by the situation in schools that provide equal access, participation, control and benefits for male and female students. Likewise, the leadership skills of students who have the ability to lead proficiently, student leadership skills are facilitated through the habituation of routine activities at school even though the school does not yet have a special programme for leadership. By creating a gender-responsive space, male and female students can optimise their leadership skills that will be useful for their future lives.